NIEFORMALNE SYSTEMY TRANSFERU WARTOŚCI MAJĄTKOWYCH - Filipkowski, Wojciech (Wydział Prawa i Administracji UAM, 2006)
This is a criminological study of the phenomenon of so called informal value (or money) transfer systems (IVTS) throughout the world. At the beginning of this paper, the author presents short characteristics of cash as a payment instrument, also widely used by criminals. Almost all the anti-money laundering regimes which have been enforced so far watch closely the flow of cash between accounts, persons or countries since it gives a great amount of versatility and anonymity for its users. Secondly, the criminals usually obtain their illicit gains in the form of cash (banknotes and coins). In order to legitimize “dirty money” they introduce it into licit financial system. This is the reason why all persons who use cash are under close investigation by institutions obliged to carry out some anti-money laundering requirements. At the same time there are several main types o f so called informal value (or money) transfer systems. They are strictly connected with certain ethnic groups or minorities, e.g. Indian, Chinese, Vietnamese, etc. Some developed centuries ago and had existed long before the banking system was created in Europe (such as Hawala, Hundi, Chop shop, Chit, Fei ch’ein). These systems have been used for one reason: to move funds from one country to another. It has been done by settling financial obligations between brokers residing in different countries (sometimes even without moving money itself). Sadly, they are being used by the criminals in order to launder their ill-gotten gains, too. In fact IVTS involve very fast, inexpensive and effective techniques to circumvent regulations. What’s more important, the terrorist have been also exploiting them in order to finance their activities. The second part of the paper contains a thorough analysis of a few examples o f IVTS. The author presents the phenomenological aspects of IVTS basing on reports of international institutions and researches done abroad. The third part of the paper contains some measures that may prevent the abuse of IVTS by organized crime or terrorist organizations. The Financial Action Task Force on Money Laundering prepared the 9 Special Recommendations on terrorist financing. One of them is recommendation number 6th which refers directly to so called “alternative remittance systems”. Another institution which deals with this phenomenon is the United States’ financial intelligence unit called Financial Crimes Enforcement Network. In 2003 it issued a list of recommendations and advice for financial institutions how to spot so called “suspicious transactions” connected to IVTS. The summary contains some general remarks on the effectiveness o f the existing anti-money laundering regimes and the situation in Poland in the light of the presented characteristics of informal value transfer systems.
INFORMAL VALUE TRANSFER SYSTEMS